Music and mood in the ensemble setting - McCoy, Kelsey (Kansas State University, 2021)
The lessons demonstrated in this report are focused on applying the mood of a piece to the music. This set of lessons was developed with my teaching philosophy and my school districts interest in Conscious Discipline in mind. Conscious Discipline (2021) is a classroom management program for schools that focuses on social emotional learning for the students. I have found this classroom management plan to be very successful in helping students control their emotions and quell any potential big issues that may arise. But I have had a hard time finding ways to incorporate it into the ensemble setting without causing major disruptions to rehearsals. This set of lessons was designed to introduce students to emotions in music and allow them to explore how they can vent their emotions into their music while they play. This set of lessons was done with all my 7th and 8th grade students in both band and orchestra classes. As a result of these lessons, I believe that my students understand how to identify the mood of a piece of music and how to incorporate that mood into their playing. Hopefully they will carry this skill into their musical playing for the rest of their lives. Throughout my time at Kansas State University, I have developed many new skills and ideas that have helped me in my ensemble teaching in both band and orchestra. Although my focus has been band, I have found that many of the techniques and methodologies can be used in both areas with some minor adjustments. Taking a second look at my teaching philosophy was eye opening for me. I have found that many things have changed since I wrote my original philosophy in undergrad. Now that I have actual teaching experience, I was able to really focus my philosophy on things that matter in the classroom. Part of my teaching philosophy focuses on teaching students to grow up and be able to express themselves emotionally which was a main reason why I developed my mood and music lessons. I was also fascinated with my Curriculum and Assessment class. While my district provides a guided curriculum for me, it was more intense when I had to create it myself. This allowed me to view curriculum and lessons in a whole new light. When I have adjusted my lesson plans in the past I never focused on the bigger picture. Now, I find myself really thinking about how the adjustments will affect the rest of the year. I have a better sense of what I need to get through and how I should pace the year. Rehearsal Techniques was also a great class to take. We were able to collaborate and share rehearsal techniques with each other from around the country. It was great to be able to hear what others are doing that works for them and adapt it to use in my own classroom. This class was very practical and allowed me to take ideas and use them immediately.
Keywords: Music; Mood; Ensemble